Succession of Gut Microbial Structure in Twin Giant Pandas During the Dietary Change Stage and Its Role in Polysaccharide Metabolism - Zhan, Mingye; Wang, Lei; Xie, Chunyu; Fu, Xiaohua; Zhang, Shu; Wang, Aishan; Zhou, Yingmin; Xu, Chunzhong; Zhang, Hemin (Frontiers in Microbiology, 2020)
Adaptation to a bamboo diet is an essential process for giant panda growth, and gut microbes play an important role in the digestion of the polysaccharides in bamboo. The dietary transition in giant panda cubs is particularly complex, but it is an ideal period in which to study the effects of gut microbes on polysaccharide use because their main food changes from milk to bamboo (together with some bamboo shoot and coarse pastry). Here, we used 16S rDNA and internal transcribed spacer 1 (ITS1) DNA sequencing and metagenomic sequencing analysis, to investigate the succession of the gut microbial structure in feces sampled from twin giant panda cubs during the completely dietary transition, and determine the abundances of polysaccharide-metabolizing genes and their corresponding microbes to better understand the degradation of bamboo polysaccharides. Successive changes in the gut microbial diversity and structure were apparent in the growth of pandas during dietary shift process. Microbial diversity increased after the introduction of supplementary foods and then varied in a complex way for 1.5–2 years as bamboo and complex food components were introduced. They then stabilized after 2 years, when the cubs consumed a specialized bamboo diet. The microbes had more potential to metabolize the cellulose in bamboo than the hemicellulose, providing genes encoding cellulases systems corresponding to glycoside hydrolases (GHs; such as GH1, GH3, GH5, GH8, GH9, GH74, and GH94). The cellulose-metabolizing species (or genes) of gut bacteria was more abundant than that of gut fungi. Although cellulose-metabolizing species did not predominate in the gut bacterial community, microbial interactions allowed the giant pandas to achieve the necessary dietary shift and ultimately adapt to a bamboo diet.